Harvesting and pre-treatment of microalgae cultivated in wastewater for biodiesel production: A review - Kadir, W.N.A. (Elsevier Ltd, 2018)
Cultivation of microalgae using wastewater has received considerable attention around the globe as a platform to remove inorganic nutrients from the wastewater and producing microalgae biomass for biodiesel production. This can be done by converting freely available nutrients from the wastewater (particularly nitrogen, N and phosphorus, P) into microalgae biomass with concomitant carbon dioxide (CO2) sequestration via photosynthesis process. In fact, microalgae biodiesel could help to reduce greenhouse gas (GHG) emissions to the atmosphere through the replacement of fossil diesel as it is made from renewable resources. Despite the various benefits to produce microalgae biodiesel, a number of technical hurdles such as complex processes, requirement of high energy input during cultivation and dewatering (harvesting steps) need to be addressed for commercialization purpose. Besides, additional pre-treatment step is necessary to disrupt the microalgae cell wall to enhance lipid extraction efficiency. Hence, this paper is aims to reveal in-depth analysis and discussions on the process of microalgae-based wastewater treatment as well as microalgae cells disruption technology for lipid extraction. The paper also includes several new directions for technological improvements to improve commercialization potential of microalgae biodiesel. Â© 2018 Elsevier Ltd